Pengaruh Hypnobirthing Terhadap Percepatan Lama Kala II Persalinan di Puskesmas Kota Yogyakarta Tahun 2010 - Susilo Rini (Universitas Harapan Bangsa Purwokerto, 2010)
Background: Five percents of delivery women through vagina get a longer delivery that is caused by a scare in facing delivery so that is can stimulate in creasing of stress hormone thatcan disturb uteric contraction and make delivery longer that it must be. A longer delivery canalso cause shock, dehydration, infection, utery inersia and fatal emergency if it doesnot getpirst aid an soon as possible. Hypnobirthing is the alternative way to stop scaring feeling. Indelivery, hypnobirthing is used to prevent longer delivery accident that is caused bypsiological factors of mothers, those are scaring feeling and anxiety in facing deliveryprosess. Objectives: The purpose of this was to know the effect of hypnobirthing to the accelerationofdelivery phased duration in Puskesmas Yogyakarta City in 2010. The Method Of this research: This study is a pure research by using Posttest Only WithControl Design. The location were in Puskesmas Mergangsan and Puskesmas Tegalrejo inJune up to July 2010. The research subjects were delivery mothers in first delivery phasedthat ful filled the criteria. Sampling technich that was used purposive sampling. Independentvariablewas hypnobirthing and dependent variable was second delivery phased duration withnominal and rasio scale with independent satatistic t-test in trusred level of 95 %. Result: From 60 respondents, 30 person (50%) got hypnobirthing (experiment group) and 30person (50%) did not get hypnobirthing (control group). The were a significant differencesbetween the two groups to the acceleration of second delivery phased with t account value3,432 and P value (0.001) < 0.05 so Ho is un acceptable it means that is the effect ofhypnobirthing to the acceleration of second delivery phased. Conclusion: Hypnobirthing in first delivery phased could accelerate the second deliveryphased. Keywords: Hypnobirthing, second delivery phased.